Effect of geocell height on behavior of sand under constant compaction energy evaluated by plate load testing in large-scale soil box - Yeontae Kim; Turab H. Jafri; Jinung Do (International Journal of Geo-Engineering)
Abstract Geocell is a reinforcing material in civil engineering that creates cell structures with multiple bands filled with fill materials inside the cells, thereby providing a ground reinforcement effect. Due to the easiness of the construction and application, geocell is suitable for rapid and temporary installation on unpaved roads. Geocells have various heights depending on manufacturing conditions. In this study, the behavior of sand reinforced with geocells having various heights was evaluated. The stress-settlement relationships of the test grounds were analyzed with a large-scale soil box system and a series of plate load tests. For additional analysis, the unit weight of the reinforced ground was measured. The performance of the system was quantified using a subgrade reaction modulus (K 30). As results, the K 30 of sand reinforced with 10 cm height geocell showed higher than that of unreinforced sand. However, for 20 cm and 30 cm height geocells, the measured K 30 were similar to or lower than that of unreinforced sand. It was discovered that as the geocell height increases, the compaction efficiency delivered to the fill material within the geocells decreases, causing lowering the engineering performance of the geocell-reinforced zone. At the end of the paper, possible scenarios of using geocells are discussed.